The Influence of The Environment on The Social Emotional Development of Early Children - Alimah, Nur; Gandini, Sri; Fauziyah, Nur (Universitas Muhammadiyah Surakarta, 2023)
Children at an early age are in the golden age, because during that period there is amazing development, both physical and emotional. In this phase, the environment plays a very important role in influencing children, because children tend to imitate what they see and witness. Children do not think whether what they see and witness is good or bad. No matter how well explained, children will be more likely to believe what they see and witness for themselves. Therefore, stimulation during the golden age is the responsibility of parents and teachers as caregivers and educators in their environment. Mainly in terms of social emotional development of early childhood. However, children's social emotional development is often sidelined. As a result, This research uses a qualitative method where data is taken from observations at PAUD Kinanti Saras, Bendo village, Nogosari, Boyolali and the results of analysis from several research journals that meet the criteria are then collected and a summary is made. The aim of this research is to explain the influence of the family environment and school environment. on the social emotional development of early childhood.